2015
DOI: 10.1038/pr.2015.125
|View full text |Cite
|
Sign up to set email alerts
|

Urinary kidney injury molecule-1 rapid test predicts acute kidney injury in extremely low-birth-weight neonates

Abstract: Background:The new urinary and serum biomarkers are discovered and are being investigated. With them we can diagnose acute kidney injury (AKI) faster and more precisely and they also have a significant role in the outcome prediction. Methods: The study included 22 extremely low-birthweight neonates who were hospitalized in the neonatal intensive care units. They were divided into two groups based on serum creatinine (SCr) level-with and without AKI. Detection and quantification of urinary kidney injury molecul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 36 publications
(57 reference statements)
0
4
0
Order By: Relevance
“…The presence of AKI in a given child was determined based on the neonatal/pediatric (n/p) RIFLE and AKIN scales. 5,23 Serum creatinine was assessed at least every 48-72 h and whenever it seemed necessary. The normal ranges of SCr used for the studied population were taken from the study of Bateman et al 24 , while the eGFR values were calculated according to the one-marker equation developed by Schwartz et al 22 The presence of sepsis in a given child was determined based on the gold standard, which continues to be a positive result of blood bacteriology, while a suspicion of sepsis was based on such clinical and laboratory criteria as apnea or deterioration of mechanical ventilation parameters, abnormalities of peripheral perfusion, abnormalities of arterial pressure, hepatomegaly and/ or splenomegaly, signs of feeding intolerance, leucopenia (<4,000/mL) or elevated white blood cell count (>10,000/mL), thrombocytopenia (<100,000/mL), immature granulocyte count (immature neutrophils/total neutrophils) >0.2, and elevated C-reactive protein (CRP) (>10 mg/L).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The presence of AKI in a given child was determined based on the neonatal/pediatric (n/p) RIFLE and AKIN scales. 5,23 Serum creatinine was assessed at least every 48-72 h and whenever it seemed necessary. The normal ranges of SCr used for the studied population were taken from the study of Bateman et al 24 , while the eGFR values were calculated according to the one-marker equation developed by Schwartz et al 22 The presence of sepsis in a given child was determined based on the gold standard, which continues to be a positive result of blood bacteriology, while a suspicion of sepsis was based on such clinical and laboratory criteria as apnea or deterioration of mechanical ventilation parameters, abnormalities of peripheral perfusion, abnormalities of arterial pressure, hepatomegaly and/ or splenomegaly, signs of feeding intolerance, leucopenia (<4,000/mL) or elevated white blood cell count (>10,000/mL), thrombocytopenia (<100,000/mL), immature granulocyte count (immature neutrophils/total neutrophils) >0.2, and elevated C-reactive protein (CRP) (>10 mg/L).…”
Section: Methodsmentioning
confidence: 99%
“…Its true incidence among this age group is actually unknown, but the risk for this complication is considerably higher in more immature neonates. 3,4 Generally, AKI occurs in as many as 56% of neonates treated in neonatal intensive care units (NICU), 5 while the mortality rate among this population with AKI ranges from 33% to 78%. 6 The search for new AKI markers is based on the poor prognosis of AKI in newborns, which is partially caused by the delay in diagnosis and therapeutic intervention.…”
Section: Introductionmentioning
confidence: 99%
“…75 Kidney Injury Molecule 1 (KIM-1) is a transmembrane protein that is upregulated in kidney injury, and elevated levels have been shown to predict AKI. 76 The AUC of several of these biomarkers -in particular NGAL and TIMP2-IGFBP7 are highly predictive for AKI, using SCr as the gold standard. 76 It is imperative that we begin to incorporate novel biomarkers into future definitions of neonatal AKI and clinical care.…”
Section: Biomarkers Of Akimentioning
confidence: 99%
“…Other authors also found such results. The studies in newborns with AKI confirmed that NGAL was an important early biomarker of AKI, but data on KIM-1 were not conclusive [24][25][26][27][28][29]. Some authors indicated its statistically significant role as an early AKI biomarker [25], while others did not [26,27].…”
Section: Discussionmentioning
confidence: 99%
“…The studies in newborns with AKI confirmed that NGAL was an important early biomarker of AKI, but data on KIM-1 were not conclusive [24][25][26][27][28][29]. Some authors indicated its statistically significant role as an early AKI biomarker [25], while others did not [26,27]. In some publications the level of NGAL elevated rapidly after the activation of a damaging factor, whereas the increase in KIM-1 concentration was associated with the occurrence of proteinuria [28,29].…”
Section: Discussionmentioning
confidence: 99%